Peran Orang Tua dalam Pembinaan Moral Remaja di Desa Karya Jaya Kabupaten Buton - Alimudin Alimudin; Abdul Rahim; Madi Madi (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study aims to analyze the role of parents in fostering adolescents' moral development and to identify the supporting and inhibiting factors in this process in Karya Jaya Village, Buton Regency. This research is motivated by the importance of adolescence as a critical developmental stage that is highly vulnerable to environmental influences, thus requiring optimal moral guidance, especially from the family as the first and primary educational institution. This research employs a qualitative descriptive approach. The research subjects consist of 30 parents and adolescents selected through purposive sampling. Data collection techniques include observation, interviews, and documentation to obtain in-depth and comprehensive data. The data analysis technique uses the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The results show that parents play a significant role in moral development through role modeling, habituation of moral and religious values, effective communication, and supervision of adolescents' behavior in daily life. Parental role modeling is a key factor in shaping adolescents’ moral behavior, as adolescents tend to imitate what they observe within the family environment. Supporting factors include harmonious family conditions, active parental involvement, and a positive social environment. Meanwhile, inhibiting factors include parents' busyness, lack of supervision, and the influence of technology and peer environment. Therefore, the role of parents is crucial in shaping positive moral behavior among adolescents.